Subjective usability review of “Sehat Jiwa” Apps - Putri Safirilla Ermadi (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Background: The prevalence of mental health problems in the Indonesian population increased significantly. The latest Riskesdas (Health Basic Survey 2018) reported that 9.8% of the population have an emotional mental disorder, increased from 6.1% in the 2013 Riskesdas. In line with the growing number of mobile phone users (including those with a smartphone), Indonesian Ministry of Health has developed